Integrating Skills in ESP - Alicia Hidalgo (Asociación Colombiana de Profesores de Ingles, 2016)
Traditional ESP teaching and learning processes focus on the differences between ESP and EFL/ESL. ESP has been considered a special kind of English in which grammar, reading and translation practice have been presented for ESP students. Following this conception, nowadays, ESP teachers at university level present students with texts from which grammar, translation and reading exercises are developed.